2016
DOI: 10.1007/s00520-016-3331-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic drug initiation during the first diagnosis and the active treatment phase of B cell non-Hodgkin’s lymphoma: a cohort study of the French national health insurance database

Abstract: The high rate of psychotropic drug initiation reflects a high level of anxiety at the initial phase of B-NHL patients' trajectory. This pharmacoepidemiological study reveals inappropriate use in some patients, which should now be investigated in lymphoma survivorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…The pattern of PD consumption found in our study is in agreement with the French PD consumption around a cancer diagnosis: In a nationwide claim database study aiming to determine the PD use in solid cancer and lymphoma, 32.1% of patients had a prevalent PD consumption during the year before the diagnosis, vs. 52.6% during the year following this diagnosis, of which anxiolytics were the most frequent . Similarly, one French study in Midi‐Pyrénées found a PD use of 32.2% in patients having a B‐cell lymphoma diagnosed, anxiolytics being the most PD used .…”
Section: Discussionsupporting
confidence: 86%
“…The pattern of PD consumption found in our study is in agreement with the French PD consumption around a cancer diagnosis: In a nationwide claim database study aiming to determine the PD use in solid cancer and lymphoma, 32.1% of patients had a prevalent PD consumption during the year before the diagnosis, vs. 52.6% during the year following this diagnosis, of which anxiolytics were the most frequent . Similarly, one French study in Midi‐Pyrénées found a PD use of 32.2% in patients having a B‐cell lymphoma diagnosed, anxiolytics being the most PD used .…”
Section: Discussionsupporting
confidence: 86%
“…Conte et al investigated the incidence of depression and anxiety using an approach similar to that of the present study with incident use of PDs as measures for depression and anxiety 13 . In total, 745 NHL patients (mean age 65.1 years, male:female ratio 1.4) were included, and incident PD use was estimated during first 8 months after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with a smaller French study investigating the incidence of psychotropic drug use during the diagnosis and active treatment phase in patients with B-NHL. Here, among 745 newly diagnosed B-NHL patients with a mean age of 65.1 years, psychotropic treatment—reflecting the possible prevalence of depression or anxiety disorders—was initiated in 31.5 %, compared to 7.6% in the general population during the same period [ 18 ]. Another study conducted by Oerlemans et al analyzed data of 489 patients with HL or DLBCL who serially completed the Hamilton Anxiety and Depression Scale [ 19 ].…”
Section: Discussionmentioning
confidence: 99%